FINANCIAL SUPPORT OF THE POPULATION IN COMMERCIAL BANKS THROUGH MORTGAGE CREDITS - Gaibullaev Rakhim Murodovich; Mardonov Saidmurot (Scholar Express Journals, 2022)
The article shows the financial support of commercial banks in the provision of housing through mortgage loans and the allocation of loans in the form of longterm interest payments. It also highlights the specifics of the theory and practice of mortgage lending in the country and offers suggestions for their further development
Keywords: Commercial Banks; Mortgage Loan; Mortgage; Housing